THE ROLE OF TOPICAL ANTIBACTERIAL AGENTS IN TREATMENT OF ACUTE OTITIS MEDIA IN CHILDREN - K. G. Dobretsov ("Paediatrician" Publishers LLC, 2013)
The article covers the issues of etiology, clinical manifestations and treatment of acute otitis media in children. The author emphasized the high prevalence of this disease, listed the spectrum of causative agents and described clinical manifestations of otitis media. It was mentioned, that usage of topical antibacterial agents is a significant additional measure to systematic antibacterial treatment. Efficacy of one of such topical agents was assessed in this study. Unlike many other topical antibacterial agents, the studied drug does not have ototoxic side effect, therefore it can be used in perforated forms of otitits media. Application of this medication in perforated stage of acute purulent otitis media allows to intensify antibacterial action of systemic antibiotic and to increase the quality of treatment.